EVOLVING SUITABLE SELECTION INDEX BY ASSIGNING EQUAL ECONOMIC WEIGHTS IN FINGER MILLET [Eleusine coracana (L.) Gaertn] - P. SRILAKSHMI, D. RATNA BABU, P.V. RAMA KUMAR AND P. ANIL KUMAR (The Journal of Research ANGRAU, 2017)
The present investigation on forty- three finger millet genotypes was carried out to arrive at a suitable selection index for selecting superior genotypes for seed yield plant-1(g). In the process of developing suitable index equal economic weights were assigned to all the eleven traits viz., plant height(cm), days to 50% flowering, days to maturity, number of productive tillers plant- 1, fingers ear-1, finger length(cm), ear weight plant-1, 1000-seed weight, and seed yield plant-1(g), seed calcium content(mg/100g), seed protein content(%). It was observed that addition of characters one by one in the construction of selection index resulted in the increased estimates of genetic advance. Finally, the index constructed using all the eleven characters, recorded maximum expected genetic advance and per cent gain over seed yield plant-1 compared to that of all 2047 possible combinations.